The Immunology and Biology of Brain Tumors - Graner, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Immunotherapy has become a viable treatment modality for a variety of cancers (and referred to as Science Magazine's "Breakthrough of the Year" in 2013, as well as ASCO's "Advance of the Year" in both 2016 and 2017). This Special Issue is focused on the relevance of immunobiology in brain tumors, touching on elements of immune suppression, immune stimulation, and the immune microenvironment, with culminations in translational immunotherapy.